Effective Food Waste Utilization: A Veritable Source of Biofuel for Nigerian Economic Sustenance and Development - A Review - Benedict O. EDENSETING; Innocent O. OBOH; Alexander A. JOCK (FUDMA Journal of Engineering and Technology, 2025)
Waste generation is on the increase as the population of Nigeria increases. The current waste management practice is becoming unsustainable in the country. Nigeria generates over 25 million tonnes as municipal solid waste with one third of it generated being kitchen waste. Demand for biofuels is rapidly growing worldwide as petroleum-based fuels are finite and environmentally unfriendly. Kitchen waste is capable of producing biogas, bioethanol and biodiesel which will afford the country affordable cleaner energy for national development. It is therefore imperative to optimize this source of renewable energy for advancement of transportation, industrial growth, power generation and overall national economic growth. Hence, this review highlights the enormous energy potential in kitchen cum domestic waste.